Adoption of E-communication applications in U.S. municipalities: The role of political environment, bureaucratic structure, and the nature of applications - Ahn, Michael J. (2011)
E-government has been touted by many as a technological answer to improve citizen participation, government accountability, and transparency by facilitating a greater level of communication and flow of public information between citizens and the government. This article examines how political environment, government structure, and the nature of individual e-government applications influence and likelihood of adoption. Using data obtained from multiple sources logistic regressions are conducted on a sample of six e-government applications that possess varying degrees of communicative and organizational impacts on the government to observe how different factors influence their adoption. Findings include a general disinclination for adopting e-government applications with high communicative impact; however, such disinclination for adopting e-government applications with high communicative impact, however, such disinclination dissipated when there was a high communicative impact; however, such disinclination dissipated when there was a high level of political competition in the area and perceived demand for online communication; active traditional channels of political communication, such as political parties and accessibility to local council members, reduced the likelihood of adoption; the preferences of the elected mayor coincided with the perceptions of nonelected officials who favor e-government applications that would reduce the workload while disfavoring applications that would increase it. - Reproduced.
Keywords: Public administration; E communication; Communication technology; Information technology; E governance